2017
DOI: 10.1016/j.jbi.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Combining multivariate statistics and the think-aloud protocol to assess Human-Computer Interaction barriers in symptom checkers

Abstract: Symptom checkers are software tools that allow users to submit a set of symptoms and receive advice related to them in the form of a diagnosis list, health information or triage. The heterogeneity of their potential users and the number of different components in their user interfaces can make testing with end-users unaffordable. We designed and executed a two-phase method to test the respiratory diseases module of the symptom checker Erdusyk. Phase I consisted of an online test with a large sample of users (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…While students were prompted early in the interview to think aloud as much as possible, additional protocol reminders to consistently encourage thinking aloud were not explicit. This is consistent with the literature showing that a well-defined think-aloud protocol can lead to increased understanding between an instructor and a student, as well as elicit greater insights into the cognitive processes of learners as they interact with a system [48][49][50].…”
Section: Multimodal Interaction Metricssupporting
confidence: 90%
“…While students were prompted early in the interview to think aloud as much as possible, additional protocol reminders to consistently encourage thinking aloud were not explicit. This is consistent with the literature showing that a well-defined think-aloud protocol can lead to increased understanding between an instructor and a student, as well as elicit greater insights into the cognitive processes of learners as they interact with a system [48][49][50].…”
Section: Multimodal Interaction Metricssupporting
confidence: 90%
“…Seven of these studies were evaluating symptom checkers as a self-contained intervention. 13,17,[19][20][21][22][23] Five of these studies were evaluating an e-consultation system that included a symptom checker 7,[31][32][33][34] and two of these studies were investigating public attitudes towards symptom checkers. 35,37 One study 17 reported that patients who were classified as less socioeconomically deprived were more likely to agree to use Internet Doctor than decline participation, although no relationship was found between socioeconomic deprivation and results in this study or between e-consultation use and socioeconomic deprivation in another study.…”
Section: Equity and Inclusionmentioning
confidence: 99%
“…Seven cross-sectional papers were included in the review. 18,19,[35][36][37][38][39] Study characteristics are summarised in Table 13. The studies were carried out in the USA, 18,36,38,39 Norway 19,37 and Sweden 35 and all but one, a conference abstract, 38 were published articles.…”
Section: Patient and Public Attitudes To Online Self-diagnosismentioning
confidence: 99%
See 2 more Smart Citations